Investigating the Combined Effect of Natural and Metal Salt Mordants on Coloring Potential of Indian Rhubarb (Rheum emodi) Natural Dye. Issue 2 (4th March 2017) - Khan, M. Ali; Shahid-ul-Islam,; Mohammad, F.
ABSTRACT: Synthetic dyes produce wide range of shades, but some of them especially azo dyes have been recently discovered to cause severe human health and environmental problems. This has motivated research activities in the exploitation of dyes from natural products for the coloration of different textile materials. In the present investigation, Indian rhubarb ( Rheum emodi ) was used as a source of natural dye for the development of deep and bright shades on premordanted woollen yarn samples. Dyeing experiments were carried on wool samples pretreated with different combinations of natural and chemical mordants such as 2.5% myrobalan + 10% alum, 2.5% myrobalan + 2% iron, and 2.5% myrobalan + 0.5% tin. The light, wash, and rub fastness properties of dyed woollen yarn samples were evaluated along with the determination of lightness ( L *), chroma ( c *), hue angle ( h °), and strength ( K / S ) values using 8% concentration of Indian rhubarb dye.